Ð˜ÑÑÐ»ÐµÐ´Ð¾Ð²Ð°Ð½Ð¸Ðµ Ð¼ÑƒÐ»ÑŒÑ‚Ð¸Ð¿Ð¾Ñ‚ÐµÐ½Ñ‚Ð½Ñ‹Ñ… ÑÐ²Ð¾Ð¹ÑÑ‚Ð² Ð½ÐµÐ¹Ñ€Ð¾ÐºÐ»ÐµÑ‚Ð¾Ðº ÑÑƒÐ±Ð²ÐµÐ½Ñ‚Ñ€Ð¸ÐºÑƒÐ»ÑÑ€Ð½Ð¾Ð¹ Ð·Ð¾Ð½Ñ‹ ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð¼Ð¾Ð·Ð³Ð° Ð² ÑƒÑÐ»Ð¾Ð²Ð¸ÑÑ… ÐºÑƒÐ»ÑŒÑ‚Ð¸Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ - Semenova, V. M.; Medvedjev, V. V.; Stajno, L. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
There is presented the analysis of literature on the biology of neural stem cells (NSCs) of subventricular zone (SZ) of lateral ventricles of brain and the own findings on culturing of SZ fragments of embryonic brain of experimental animals on an adhesive substrate. The biological properties and multipotency of differentiation of embryonic NSCs in neuronal and glial directions under culturing have been shown.